Catalytic and MW-Assisted Michaelis-Arbuzov Reactions - Dzielak, Anna; Mucha, Artur (Current Green Chemistry, 2015)
Novel tendencies in the induction of the Michaelis-Arbuzov reaction become apparent when studying the current literature on the preparation of organophosphorus compounds. These alternatives involve catalysis with either metal salts and complexes or the application of metallic and non-metallic Lewis acids, microwave irradiation and performing the reaction in ionic liquids. The outcome of these developments is broadening the structural diversification of potential substrates and products, as well as the economic aspects by saving time and costs. In this review, we illustrate these achievements with representative examples and mechanistic discussions.
Keywords: nucleophilic substitution